Air distribution and balance in ACMV system - Chiang, Evan Wei Kian (2019)
To balance in an ACMV system is sustaining the flow of air and pressure in the system. Distributed cooperative control-based air balancing (DCC-AB) method will be executed in the midst of system operation without hindering the normal service of ventilation, which will prevent disturbance to the occupants and maintenance shutdown that can cause financial losses. The aspect of balancing provides opportunities to achieve specific supply of air under loads, which shows potential of saving a large number of energies. The aim of the experiment is to compute the flow of air and calibrating the dampers to achieve a desired airflow. Software simulations will be used to adjust the system as calculation approaches will not be precise enough. Measurements of the flow and pressures of the system will be taken down and subsequently the adjustments of the damper. The flows and adjustments process will repeat until the designed flow have be met. The calculation for each adjusted damper will take a lot time to retrieve and will be less accurate if by testing it out on the hardware right away. With software simulation, the angle for the dampers to tilt to will be done faster and measurements can be done with reference to the results obtained. This process can be done in a faster rate and cheaper at the same time.